Skrining Aktivitas Antibakteri Bakteriosin dari MinumanCe Hun Tiau - Sari, Rafika; Deslianri, Lia; Apridamayanti, Pratiwi (UI Scholars Hub, 2016)
Lactic acid bacteria is one of the beneficial bacteria because it can produce an antimicrobial peptide called bacteriocin. Bacteriocin has been applied as a natural food preservative because it effectively prevents the growth of pathogenic bacteria in food or drink. This study aims to identify the lactic acid bacteria as producers of bacteriocin from Ce hun tiau which have inhibitory activity againts pathogenic bacteria such as Escherichia coli, Staphylococus aureus and Salmonella typhi. In this study, Lactic acid bacteria were isolated from Ce Hun Tiau using streak plate method on media deMan Rogose Sharpe. Screening bacteriocin using disc diffusion method to find out the inhibitory activity of isolates against Escherichia coli, Staphylococus aureus and Salmonella typhi and for confirmation test using proteolytic enzymes. The results showed 1 isolate of lactid acid bacteria was succesfully isolated from Ce hun tiau, identified as Lactobacillus plantarum. This isolate could inhibit the growth of pathogenic bacteria Escherichia coli, Staphylococus aureus and Salmonella typhi which is a bacteriocin activity.